Data-Driven Decision-Making in Retail - Jasrotia, Manojdeep Singh; Koranchirath, Nithin Narayan (Journal of Global Economy, Business and Finance, 2025)
This study does a deep dive into potential use cases that a Retail company can take advantage of. Here, we try to explain how data driven decision making can boost Retail business. By presenting practical predictive analysis, statistical modeling, deep learning, a retail worker working in the B2B space can transform their business with their transactional logs, customer reviews, etc.Furthermore, the study tries to explain models that can be used in each of the use cases and the working algorithm behind it. It also covers how to assess those model performance and do a necessary model performance check.